Analisis Persebaran Toko Parfum di Lowokwaru Malang Menggunakan QGIS untuk Optimalisasi Lokasi Bisnis - UNEJ, DIGIMAS (Universitas Jember, 2025)
This community service aims to analyze the distribution of perfume stores in the Lowokwaru District, Malang City, which has not been extensively analyzed thematically. However, Lowokwaru is a district with high economic activity and a strategic position in Malang City. To support business decision-making, adequate spatial data is needed to analyze the distribution pattern of perfume stores. In its implementation, a field survey was conducted to collect primary data, including the location of perfume stores, the characteristics of the area, and its accessibility. The collected data was then processed and analyzed using Quantum GIS (QGIS) software to examine the distribution pattern of perfume stores in the area. The results of this community service show that perfume stores are concentrated in areas with high accessibility, such as around campuses, shopping centers, and busy commercial areas. Meanwhile, other areas, such as residential and suburban areas, show market potential that has not been optimally utilized. These findings provide opportunities for business owners to design more effective marketing strategies and expand their reach to underserved areas.